2017
DOI: 10.1111/ajr.12362
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding beyond the big smoke: Who provides support for mothers in rural Western Australia?

Abstract: Antenatal group education is effective in supporting breastfeeding duration for rural women and should be a key priority for rural health service providers. Health professionals are common sources of breastfeeding support postnatally, however creating and maintaining positive and supportive social networks for mothers might also contribute to increasing the proportion of rural infants who meet the World Health Organization guidelines for exclusive breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In addition, more parents from rural areas were unemployed, and less likely to breastfeed children. This was in line with a study conducted in Australia, where health professionals were the main supporters of breastfeeding [30]. Moreover, in rural populations from Serbia, parents are taking their children to the doctor in fewer cases.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, more parents from rural areas were unemployed, and less likely to breastfeed children. This was in line with a study conducted in Australia, where health professionals were the main supporters of breastfeeding [30]. Moreover, in rural populations from Serbia, parents are taking their children to the doctor in fewer cases.…”
Section: Discussionsupporting
confidence: 88%
“…Although several researchers have concluded that breastfeeding outcomes are improved following prenatal education (Cox et al, 2017), Lumbiganon and colleagues' (2016)…”
Section: Outcomes Of Breastfeeding Information Seekingmentioning
confidence: 99%
“…Whereas sources of infant feeding information mirror those for general motherhood topics, the attitudes and knowledge of those around mothers play a large role in shaping information behavior (Rollins et al, 2016; Spiro, 2016). Other sources of information about breastfeeding include community-based peer groups (Shakya et al, 2017), the infant’s grandmother(s) (Cox, Giglia, & Binns, 2017; Karmacharya, Cunningham, Choufani, & Kadiyala, 2017), and online social networks (Gray, 2013; McKeever & McKeever, 2017). Although a number of researchers have found that the most influential person in the initial decision to breastfeed is the infant’s father (Sherriff, Hall, & Panton, 2014), fathers have rarely been singled out as an information source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation